The essential genome of the crenarchaeal model Sulfolobus islandicus - Changyi Zhang (Nature Portfolio, 2018)
Sulfolobus islandicus is a model organism within the TACK superphylum of the Archaea. Here, the authors perform a genome-wide analysis of essential genes in this organism, show that the proteinaceous S-layer is not essential, and explore potential stages of evolution of the essential gene repertoire in Archaea.